Narrative Construction of the Qur'anic Story: A Structural and Functional Approach - Mardan, Mardan (Jurnal Adabiyah, 2026)
In addition to containing teachings on faith, worship, and morals, the Quran also presents stories that have educational, persuasive, and transformative functions for human life. These stories are not intended as historical writing in the chronological sense, but rather as a means of preaching to provide guidance, warnings, and admonition. This study aims to examine the meaning, existence, scope, and characteristics of stories in the Quran, focusing on the nature of the stories, their types, their constituent elements, and the purpose of their presentation. This study uses a structural-semiotic approach and structural-functional analysis, placing Quranic verses containing stories as the main text of the study. The results of the discussion indicate that Quranic stories are true events and contain key narrative elements in the form of events, characters, and dialogue, presented in a sophisticated style and rich with symbolic meaning. These stories serve to reinforce religious values, clarify the principles of da'wah (Islamic propagation), provide moral examples, and strengthen belief in the truth of the Quranic message. Thus, the study of Quranic stories is not only important from a religious perspective but is also relevant in literary and linguistic studies as a manifestation of the miraculous nature of the Quranic language. ملخص يحتوي القرآن الكريم، بالإضافة إلى تعاليمه في الإيمان والعبادة والأخلاق، على قصص ذات وظائف تعليمية وإقناعية وتغييرية في حياة الإنسان. هذه القصص ليست سردًا تاريخيًا بالمعنى الزمني، بل هي وسيلة للدعوة والتوجيه والتحذير والنصح. تهدف هذه المقالة إلى دراسة معنى القصص في القرآن الكريم، ووجودها، ونطاقها، وخصائصها، مع التركيز على طبيعتها، وأنواعها، ومكوناتها، والغاية من عرضها. يستخدم هذا البحث المنهج السيميائي البنيوي والتحليل الوظيفي البنيوي، مع اعتبار آيات القرآن الكريم التي تتضمن قصصًا النص الرئيسي للدراسة تشير نتائج المناقشة إلى أن القصص القرآنية أحداثٌ حقيقية، وتحتوي على عناصر سردية أساسية في شكل أحداث وشخصيات وحوار، مُقدَّمة بأسلوبٍ راقٍ وغني بالمعاني الرمزية. تُسهم هذه القصص في ترسيخ القيم الدينية، وتوضيح مبادئ الدعوة، وتقديم الأمثلة الأخلاقية، وتعزيز الإيمان بصدق رسالة القرآن. لذا، فإن دراسة القصص القرآنية لا تقتصر أهميتها على الجانب الديني فحسب، بل تتعداه إلى الدراسات الأدبية واللغوية، باعتبارها تجليًا لطبيعة اللغة القرآنية العجيبة. Abstrak Al-Qur’an selain memuat ajaran akidah, ibadah, dan akhlak, juga menyajikan kisah-kisah yang memiliki fungsi edukatif, persuasif, dan transformatif bagi kehidupan manusia. Kisah-kisah tersebut tidak dimaksudkan sebagai penulisan sejarah dalam arti kronologis, melainkan sebagai sarana dakwah untuk memberikan petunjuk, peringatan, dan i‘tibar. Artikel ini bertujuan untuk mengkaji makna, eksistensi, cakupan, serta karakteristik kisah dalam Al-Qur’an dengan menitikberatkan pada hakikat kisah, jenis-jenis kisah, unsur-unsur pembentuk, serta tujuan penyajiannya. Penelitian ini menggunakan pendekatan struktural semiotik dan analisis struktural fungsional dengan menempatkan ayat-ayat Al-Qur’an yang mengandung kisah sebagai teks utama kajian. Hasil pembahasan menunjukkan bahwa kisah Al-Qur’an merupakan peristiwa yang benar-benar terjadi dan memiliki unsur-unsur naratif utama berupa peristiwa, tokoh, dan dialog, yang disajikan dengan gaya bahasa tinggi dan sarat makna simbolik. Kisah-kisah tersebut berfungsi untuk meneguhkan nilai-nilai keimanan, memperjelas prinsip-prinsip dakwah, memberikan keteladanan moral, serta memperkuat keyakinan terhadap kebenaran risalah Al-Qur’an. Dengan demikian, kajian terhadap kisah Al-Qur’an tidak hanya penting dari perspektif keagamaan, tetapi juga relevan dalam kajian sastra dan linguistik sebagai wujud kemukjizatan bahasa Al-Qur’an.